1960
DOI: 10.2307/1365656
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization in the Anatidae and Its Taxonomic Implications

Abstract: Without doubt, waterfowl of the family Anatidae have provided the greatest number and variety of bird hybrids originating from both natural and captive conditions. The recent compilation by Gray (1958) has listed approximately 400 interspecies hybrid combinations in this group, which are far more than have occurred in any other single bird family. Such a remarkable propensity for hybridization in this group provides a great many possibilities for studying the genetics of speciation and the genetics of plumage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
2

Year Published

1975
1975
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 2 publications
3
40
0
2
Order By: Relevance
“…Bird egg whites, sera, and tissue extracts were obtained, prepared, and stored as described (10 Table 1 gives further details regarding the classification of the species examined. This constituted a representative sample of hybridizable species pairs, since more than half of all reported cases of avian interspecific hybrids occur within the orders Anseriformes and Galliformes (11)(12)(13). We prepared antisera (see below) to albumin from six species and to transferrin from five species and made immunological comparisons of the proteins of 36 different avian species pairs capable of interspecific hybridization.…”
Section: Methodsmentioning
confidence: 99%
“…Bird egg whites, sera, and tissue extracts were obtained, prepared, and stored as described (10 Table 1 gives further details regarding the classification of the species examined. This constituted a representative sample of hybridizable species pairs, since more than half of all reported cases of avian interspecific hybrids occur within the orders Anseriformes and Galliformes (11)(12)(13). We prepared antisera (see below) to albumin from six species and to transferrin from five species and made immunological comparisons of the proteins of 36 different avian species pairs capable of interspecific hybridization.…”
Section: Methodsmentioning
confidence: 99%
“…This represents the first documented case of interspecific pair-bonding and out-crossing of the Bufflehead with the Common Goldeneye (Johnsgard 1960(Johnsgard , 1965Bellrose 1976;Gauthier 1993;Gillham and Gillham 2002). Hybridization of the Common Goldeneye has been reported with Barrow's Goldeneye, White-winged Scoter (Melanitta fusca), Common Merganser (Mergus merganser) and Hooded Merganser, and Smew (Johnsgard 1965).…”
Section: Discussionmentioning
confidence: 85%
“…However, because they are so similar and there is such fierce competition with goldeneyes, one would expect such animosity to suppress mutual attraction. Furthermore, although hybridization occurs much more frequently amongst waterfowl than any other family (Johnsgard 1960;Tubaro and Lijtmaer 2002) and monogamy tends to be the family rule, Mayr (1942) found that hybrids occurred much more rarely among monogamous species. And Buffleheads are strongly monogamous, with a ritualized courtship display very different from that of the Common Goldeneye.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such variation caused by hybridization have been occasionally reported in waterfowl (Johnsgard 1960(Johnsgard , 1965McCarthy 2006). Gender-related anomalies, such as gynandromorphism and intersex, are also accompanied by unusual plumages or abnormal external features (Witschi 1961).…”
Section: Introductionmentioning
confidence: 91%